Characterization of Chemical Compounds and Antioxidant Activity of Centaurea solstitialis sp. schouwii (DC.) Q. et S. (Asteraceae) - Aliouche, Lamia; Mosset, Paul; León, Francisco; Brouard, Ignacio; Benayache, Samir; Sarri, Djamel; Benayache, Fadila (Current Bioactive Compounds, 2020)
Background: The antioxidant activity and the total phenolic and flavonoid contents of the derived extracts (chloroform, ethyl acetate and n-butanol) of the 70% hydroalcoholic extract of the aerial parts of Centaurea solstitialis growing in Algeria was assessed. The active extracts were selected for phytochemical investigations. Methods: The antioxidant capabilities of the extracts were assessed using 1, 1-diphenyl-2- picrylhydrazyl radical (DPPH•) scavenging and Cupric Ion Reducing Antioxidant Capacity (CUPRAC) assays. Butylhydroxyanisole (BHA), butylhydroxytoluene (BHT) and α –tocopherol were used as positive controls. The total phenolic content and total flavonoid content of the extracts were determined as gallic acid equivalents and quercetin equivalents, respectively. Chromatographic methods were used to isolate the secondary metabolites and spectrometric and spectroscopic methods were used to determine their chemical structures. Results: The ethyl acetate extract exhibited the highest antioxidant activities followed by the n-butanol extract. The highest phenolic and flavonoid contents were found in the n-butanol extract. Phytochemical study of the ethyl acetate and n-butanol extracts led to the isolation of an undescribed guaianolide named 3-(4-hydroxybenzoyl)-cynaratriol and a known sesquiterpene lactone along with three known flavonoid glycosides. Their structures were established by spectral analyzes mainly high resolution electrospray ionisation mass spectrometry (HR-ESIMS) and 1D and 2D nuclear magnetic resonance experiments. Conclusion: The extracts of aerial parts of C. solstitialis showed significant antioxidant activities. An undescribed sesquiterpene lactone and four known secondary metabolites were isolated from the most active extracts.
Keywords: antioxidant activity